Spaces of social reproduction, mobility, and the Syrian refugee care crisis in Izmir, Turkey - Acara, Eda; Özdemir, Sevim (Urban geography, 2023)
This article explores how European border management policies, together with Turkey's stratified citizenship system for Syrian refugees and Turkish nationalism, shape the urban daily lives of Syrian women refugees in Izmir, Turkey. In 2019 we conducted in-depth interviews and a mapping exercise with 20 Syrian refugee women in Izmir to explore how their urban mobility patterns and struggles to access spaces of social reproduction shape gendered and racialized relations within the city of Izmir. Most Syrian refugees live in extreme poverty and their encounters with public spaces in Izmir are shaped by a stratified citizenship system. Together with the profitability of the exploitation of immigrant labor, this system's neoliberal and patriarchal peculiarities place social reproduction duties on women's shoulders. Women's reproductive and care-giving responsibilities constitute the core of their relationship with the city and their cartographies of urban mobility. Turkey's ambiguous "temporary protection" regime combined with racialized nationalism produce gendered interior borders which shape Syrian women's their mobility and access to spaces of social reproduction, such as parks and hospitals, in the city of Izmir.